2011
DOI: 10.12681/mms.54
|View full text |Cite
|
Sign up to set email alerts
|

New records of the genus Pachygrapsus (Crustacea: Decapoda) from the central Mediterranean Sea with a review of its Mediterranean zoogeography

Abstract: The occurrence of Pachygrapsus maurus and Pachygrapsus transversus is reported from the Maltese Islands for the first time on the basis of one specimen of P. maurus collected in 1990 and numerous recent specimens, and the distribution of the two species is mapped. The controversial presence of P. maurus in Italy is confirmed and two new sites for this species are reported, including the first for the mainland of Italy. The examination of the historical specimen of P. maurus from the Genova area revealed a misi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…This is the first record of P. maurus from the southeastern coast of Sicily and adds new data about its habitat in the Mediterranean Sea. Furthermore, with the exception of the doubtful record by Magrì (1911) (see Crocetta et al, 2011), we can consider our record as the first welldocumented finding of the species along the Ionian coast of Sicily. Pipitone & Arculeo (2003) and Froglia (2010) did not include the presence of the species in eastern Sicily, while it was previously recorded from the northwestern coast of the island (Misuri, 1914).…”
Section: First Record Of the Blue Crabsupporting
confidence: 50%
See 1 more Smart Citation
“…This is the first record of P. maurus from the southeastern coast of Sicily and adds new data about its habitat in the Mediterranean Sea. Furthermore, with the exception of the doubtful record by Magrì (1911) (see Crocetta et al, 2011), we can consider our record as the first welldocumented finding of the species along the Ionian coast of Sicily. Pipitone & Arculeo (2003) and Froglia (2010) did not include the presence of the species in eastern Sicily, while it was previously recorded from the northwestern coast of the island (Misuri, 1914).…”
Section: First Record Of the Blue Crabsupporting
confidence: 50%
“…The number of post-orbital spines allows immediate identification of P. marmoratus: 3 in this species versus 2 in P. maurus and P. transversus. Finally, the presence (P. transversus) or the absence (P. maurus) of 2-3 apical spines on the posterior edge of the meropodite of the fifth pereiopod allows discriminating between these two latter species (Crocetta et al, 2011).…”
Section: Spreading Of the Invasive Crab Percnon Gibbesi Along The Apumentioning
confidence: 99%
“…This suggests that the species might have maintained a low profile on the beach through low individual abundances, such that it went largely undetected. To this it should be also added that shore decapods largely suffer from a lack of studies, as recently suggested by Crocetta et al (2011) while recording two Pachygrapsus Randall, 1840 species in the same area. Nevertheless, the confirmed occurrence of the species in such high densities on at least three Maltese beaches puts the onus now on the Maltese environmental authorities to adopt conservation measures to safeguard the protected status of the species, given the popularity of Maltese beaches during the bathing season.…”
Section: Discussionmentioning
confidence: 99%
“…Gobius couchi, Millerigobius macrocephalus and Zebrus zebrus; see Kovačić et al, 2013) but in other cases it appears that a recent range expansion from elsewhere in the Mediterranean is more plausible (e.g. Pachygrapsus maurus and P. transversus; see Crocetta et al, 2011; Lobotes surinamensis; see Deidun et al, 2010). As with any inventory, a line has to be drawn somewhere determining what will be included and what will not.…”
Section: Discussionmentioning
confidence: 99%